2011
DOI: 10.1097/aog.0b013e31821bdd16
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism and Use of Prophylaxis Among Women Undergoing Laparoscopic Hysterectomy

Abstract: Whereas patients undergoing laparoscopic hysterectomy are overall at low risk for venous thromboembolism, older women, those with medical comorbidities, and women with cancer are at substantial risk. Venous thromboembolism prophylaxis is highly variable and often not utilized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Patients who received mechanical prophylaxis in combination with pharmacologic prophylaxis were coded as having received combination prophylaxis. 20 Two separate end points were analyzed. Any prophylaxis was defined as having received mechanical, pharmacologic, or combination prophylaxis.…”
Section: Methodsmentioning
confidence: 99%
“…Patients who received mechanical prophylaxis in combination with pharmacologic prophylaxis were coded as having received combination prophylaxis. 20 Two separate end points were analyzed. Any prophylaxis was defined as having received mechanical, pharmacologic, or combination prophylaxis.…”
Section: Methodsmentioning
confidence: 99%
“…Limited studies have estimated the rate of VTE in patients with gynecologic cancer undergoing minimally invasive surgery, reporting results lower than 2,4% [7,19,20]and thus implying that this group of patients are at lower risk for postoperative venous thromboembolic events than their open counterparts. These lower rates could be however attributed to the use of some kind of prophylaxis.…”
Section: Risk Factorsmentioning
confidence: 98%
“…Limited data have so far demonstrated that the rate of VTE in patients undergoing laparoscopic surgery is low, even in oncologic patients [7]. However, the necessity of thromboprophylaxis in minimal invasive surgery remains debatable.…”
Section: Introductionmentioning
confidence: 99%
“…While we chose bundle items based on associations with surgical site infection, other items may be included that have evidence for decreasing postoperative complications like prehabilitation before surgery, VTE prophylaxis, early ambulation, and chlorohexidine gluconate-based skin hygiene. 6,[24][25][26] Implementing the concept of a bundle of processes into institution-wide practice may be a relatively simple intervention that identifies and minimizes unnecessary variation in care to improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%